2018
DOI: 10.1007/s13105-018-0626-0
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of diabetes-related liver injury by the HMGB1/TLR4 inflammatory pathway

Abstract: Chronic inflammation plays an essential role in the development of diabetic complications. Understanding the molecular mechanisms that support inflammation is a prerequisite for the design of novel anti-inflammatory therapies. These would take into consideration circulating levels of cytokines and damage-associated molecular patterns (DAMPs) that include the high mobility group box 1 (HMGB1) protein which, in part, promotes the inflammatory response through TLR4 signaling. The liver, as the source of circulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 45 publications
(63 reference statements)
1
9
0
Order By: Relevance
“…In agree with this opinion, the present study found that supplementation with BHB exacerbated LPS/ d ‐Gal‐induced liver injury. In addition, the present study found that supplementation with BHB enhanced LPS/ d ‐Gal‐induced inflammation, and several reports shown that treatment with anti‐inflammation agents prevented diabetes‐associated liver injury . Therefore, the proinflammatory activities of BHB might be involved in the development of diabetes‐associated liver injury.…”
Section: Discussionsupporting
confidence: 71%
“…In agree with this opinion, the present study found that supplementation with BHB exacerbated LPS/ d ‐Gal‐induced liver injury. In addition, the present study found that supplementation with BHB enhanced LPS/ d ‐Gal‐induced inflammation, and several reports shown that treatment with anti‐inflammation agents prevented diabetes‐associated liver injury . Therefore, the proinflammatory activities of BHB might be involved in the development of diabetes‐associated liver injury.…”
Section: Discussionsupporting
confidence: 71%
“…In the liver tissue of streptozotocin‐induced diabetic rats, HMGB1‐TLR4 signalling is activated, accompanied by the activation of MAPK (p38, ERK, JNK), NFκB‐p65 and JAK1/STAT3 signalling pathways, which contributes to systemic inflammation ( Figure 2C). 50 Hyperhomocysteinemia (HHcy) induces expression and secretion of HMGB1 in vascular endothelial cells, which is regulated by Neuropilin‐1 (NRP1)‐p38 MAPK axis 51 . Vascular endothelial cell inflammation and dysfunction are common complications of diabetes that is controlled by hyperglycaemia‐induced miR‐106 and subsequent induction of HMGB1 expression and inflammation 52 …”
Section: Extracellular Function Of Hmgb1 In Metabolic Diseasesmentioning
confidence: 99%
“…The growing evidence now supports that free fatty acids can activate inflammatory signaling through different mechanisms including activation of the innate immune toll-like receptors (TLRs) [23,24]. TLR4, a member of the family of pattern-recognition receptors, activates the innate immune response after interaction with pathogen-associated molecular patterns including lipids, proteins, lipoproteins and LPS, as well as damage-associated signals or alarmins, e.g., high-mobility group box-1 protein (HMGB1) [25,26]. Binding of cognate ligands to TLRs activates two types of intracellular signaling pathways: One that requires myeloid differentiation factor-88 (MyD88) as an adaptor protein or another that involves the Toll/interleukin-1 receptor (TIR) domain-containing adaptor protein inducing IFNβ (TRIF).…”
Section: Introductionmentioning
confidence: 99%